Health-related quality of life among haemophilia children in Hospital Universiti Sains Malaysia - Nabir, Azie Jumaatul Adawiyah (2017)
Background Haemophilia is one of the most common genetic disorders in the world. It is caused by factor VIII deficiency in haemophilia A and factor IX deficiency in haemophilia B. These factors are important in human body coagulation system. Patients with these disorders are exposed to the risk of excessive bleeding that occur either spontaneous or trauma. Thus, they would need factor replacement therapy either as prophylactic therapy or on-demand need to reduce the risk of any bleeding complication such as neurological abnormality post intracranial bleeding, joint deformity, transfusion transmitted infection such as hepatitis B, C or HIV and even death. As any other chronic illnesses, haemophilia does not only affect patient’s physical function but also their emotional, psychosocial and school function. This research is aimed on evaluating health-related quality of life among paediatric patients with haemophilia using translated and validated questionnaire PedsQLTM 4.0 Generic Core Scale. Objective To study the health-related quality of life (HRQOL) among children with haemophilia who received treatment in Hospital Universiti Sains Malaysia. Methodology This study involved all 12 haemophilia patients who received treatment or came for follow up at Paediatric Clinic Hospital USM, Haemato-oncology ward Hospital USM until April 2017. PedsQL TM 4.0 Generic Core Scale self-report and parents’ reports were used. Wilcoxonsigned-rank test was used to compare the level of each patient HRQOL from patient’s own perspective and the caregiver’s perspective. Results: All twelve Haemophilia A patients in Hospital USM were male with median age of 16 years old. Overall health-related quality of life of the haemophilia patient was good especially in physical domain with score of 90 (83,99) and social domain with score of 90 (80,99). Meanwhile, the lowest score was in school function domain with score of 68 (60,75) especially in item of missed school during unwell and for hospital visit. Total median scored for healthrelated quality of life reported by parents was lower compared with child self-report with score of [81 (75,89), 75 (73,83), z score -2.09, p value 0.037]. Parents-proxy reported lower score especially in emotional function domain [85 (76,94), 75 (58,85) z score -2.12, p value 0.034] and social function domain [90 (80,94), 80 (71,89)) z score -1.98, p value 0.047]. Conclusion: Health-related quality of life (HRQOL) among children with haemophilia that received treatment in Hospital Universiti Sains Malaysia was good. Parents and child both agreed that school function domain was affected due to missed school during unwell and for hospital visit. Parents perceived differently on their child HRQOL especially in social and emotional function.